PENGARUH KARAKTERISTIK UNIT HUNIAN TERHADAP KEPUASAN BERMUKIM PENGHUNI PERUMAHAN - Nahdatunnisa, Nahdatunnisa; Tahir, M. Arzal; Wardiningsih, Wardiningsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The rapid population growth and urbanization in major cities across various developing countries have increased the demand for urban infrastructure, including housing. As projected in the Sustainable Development Goals (SDGs), by the year 2030, more than 60% of the population is expected to reside in urban areas. Meeting housing needs is a fundamental requirement for humans that evolves according to different life stages. This study aims to examine the effect of housing characteristics on residential satisfaction in simple housing in the city of Kendari. The research type is explanatory, with the research population consisting of type 36 houses. The sample size is set at 195 units, and data collection was carried out using questionnaires. The data were analyzed with structural equation modeling (SEM) using AMOS version 24 to obtain causal relationships between the variables developed in this study. The results indicate that the effect of housing unit characteristics on residential satisfaction has a path coefficient of 0.01 with a probability level of 0.968. These findings suggest a positive effect of housing unit characteristics; however, this effect is not significant in relation to the level of residential satisfaction among occupants of simple housing.